Mencapai Target Sustainable Development Golas’s (SDG’s) di Desa Sermong Kecamatan Taliwang Kabupaten Sumbawa Barat Tahun 2021 - Ilham Zitri; Arfy Rosiastawa; Amil; Ayatullah Hadi (Journal of Social and Policy Issues, 2023)
Development is a social reality that is directly related to community activities and all its social aspects, including actions, behaviors, perceptions, social interactions, and the social structure of society within them. In this context, women are part of a social structure that has strategic roles and functions, so involving them in the development process is a must. The purpose of conducting this research is to find out the participation of women in achieving the target of Sustainable Development Goals in Sermong Village, Taliwang District, West Sumbawa Regency in 2021, the research method in this study is a qualitative approach using observation, interview and documentation data collection methods, data analysis methods using data collection , data reduction, data presentation and conclusion. The results of this study are the target of Sustainable Development Goals implemented in Sermong Village in 2021, namely Village Without Poverty, where women participate in the thinking stage and planning stage, in the thinking stage women participate in giving aspirations to participate in the management of Sustainable Development Goals volunteers, and at the planning stage women participate in management to collect population data to design targets for the Sustainable Development Goals in 2021. Women's involvement is quite good in achieving the Sustainable Development Goals targets in Sermong Village in 2021 because 17 of the volunteer members of the Sustainable Development Goals 5 are women